Hubungan Luar Negeri Aktor Subnasional: Kasus Kabupaten Garut di Indonesia dan Damyang-gun di Korea Selatan - Haritsa Shafiyah; Gilang Nur Alam; R. M. T. Nurhasan Affandi (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2021)
This article explains how foreign relations are carried out by subnational actors in Indonesia. In carrying out foreign relations or other international activities, subnational actors must follow the rules and regulations set by the central government. For example, Kabupaten Garut, one of Indonesia’s sub-national actors, carries out foreign relations with Damyang-gun, South Korea, based on the existing national laws and regulations on foreign relations. This foreign relationship occurs because both Garut and Damyang-gun need each other to fulfil their own interests. This article discusses this foreign relations by using Christopher Whytock’s theory of transgovernmentalism and Alexander Kuznetsov’s paradiplomacy view. Employing a descriptive-analytic method, this article collected its required data through interviews and literature study. The findings show that as seen in the case of Garut and Damyang-gun foreign relations by sub-national actors that are carried out based rules and regulations resulted in positive outcomes for both the regional and central governments.